Rimonabant Kills Colon Cancer Stem Cells without Inducing Toxicity in Normal Colon Organoids - Fiore, Donatella; Ramesh, Prashanthi; Proto, Maria C.; Piscopo, Chiara; Franceschelli, Silvia; Anzelmo, Serena; Medema, Jan P.; Bifulco, Maurizio; Gazzerro, Patrizia (Frontiers in Pharmacology, 2018)
Colorectal cancer (CRC), like other tumor types, is a highly heterogeneous disease. Within the tumor bulk, intra-tumoral heterogeneity is also ascribable to Cancer Stem Cells (CSCs) subpopulation, characterized by high chemoresistance and the unique ability to retain tumorigenic potential, thus associated to tumor recurrence. High dynamic plasticity of CSCs, makes the development of winning therapeutic strategies even more complex to completely eradicate tumor fuel. Rimonabant, originally synthesized as antagonist/inverse agonist of Cannabinoid Receptor 1, is able to inactivate Wnt signaling, both in vitro and in vivo, in CRC models, through inhibition of p300-histone acetyltransferase activity. Since Wnt/β-Catenin pathway is the main player underlying CSCs dynamic, this finding candidates Rimonabant as potential modulator of cancer stemness, in CRC. In this work, using established 3D cultures of primary colon CSCs, taking into account the tumor heterogeneity through monitoring of Wnt activity, we demonstrated that Rimonabant was able to reduces both tumor differentiated cells and colon CSCs proliferation and to control their survival in long term cultures. Interestingly, in ex vivo model of wild type human organoids, retaining both architecture and heterogeneity of original tissue, Rimonabant showed no toxicity against cells from healthy colon epithelium, suggesting its potential selectivity toward cancer cells. Overall, results from this work provided new insights on anti-tumor efficacy of Rimonabant, strongly suggesting that it could be a novel lead compound for CRC treatment.